Програмна система для переробки харчових відходів в нові продукти харчування «productsrise» - Авдєєв, О. Д. (ХНУРЕ, 2020)
Between 33-50% of all food produced globally is never eaten, and the value of this wasted food is worth over $1 trillion. To put that in perspective, in the USA food waste represents 1.3% of the total GDP. Food waste is a massive market inefficiency, the kind of which does not persist in other industries. Food waste ends up wasting nearly a quarter of water supply in the form of uneaten food or over $172 billion in wasted water. For example, each year, USA spend over $220 billion growing, transporting, and processing almost 70 million tons of food that ends up going to waste. Growing food that goes to waste ends up using up 21% of our freshwater, 19% of our fertilizer, 18% of our cropland, and 21% of our landfill volume.